Quadrant of Difficulty-Usefulness (QoDU) as New Method in Preparing for Improvement of E-learning in Health College - Nugroho HSW; Suparji S; Sunarto S; Handoyo H; Yessimbekov Z; Burhanuddin N; Selasa P (Dove Medical Press, 2020)
Heru Santoso Wahito Nugroho,1 Suparji Suparji,1 Sunarto Sunarto,1 Handoyo Handoyo,2 Zhanibek Yessimbekov,3 Nurfardiansyah Burhanuddin,4 Pius Selasa5 1Midwifery Department, Poltekkes Kemenkes Surabaya, Surabaya, Jawa Timur, Indonesia; 2Environmental Health Department, Poltekkes Kemenkes Surabaya, Surabaya, Jawa Timur, Indonesia; 3Food Engineering Department, Shakarim State University, Semey, East Kazakhstan Region, Kazakhstan; 4Public Health Department, Universitas Muslim Indonesia, Makassar, Indonesia; 5Nursing Department, Poltekkes Kemenkes Kupang, Kupang, Nusa Tenggara Timur, IndonesiaCorrespondence: Heru Santoso Wahito NugrohoPoltekkes Kemenkes Surabaya, Pucang Jajar Tengah 56, Surabaya, Jawa Timur 60282, IndonesiaTel +6282142259360Fax +62315028141Email heruswn@gmail.comBackground: Many educational institutions around the world are implementing e-learning, but there are still many technical obstacles. Relatively many elements of e-learning must be improved in performance, so which elements should be selected which are prioritized to be improved first.Methods: This research applied a new method in order to select e-learning elements of health professionals’ education that will be prioritized for improvement. This new method was called the Quadrant of Difficulty-Usefulness (QoDU). The subjects of this study were 200 students of Environmental Health School of Magetan, Indonesia.Results: The elements that were sorted by priority were learning design, handout, book, link to resources, discussion forum, chatting, assignment, feedback, quiz and survey. The attributes used as the basis for determining priorities were difficulty and usefulness. Data regarding attributes were obtained through filling out the questionnaire. For each element the following were determined: 1) difficulty and usefulness; 2) mean score of difficulty and mean score of usefulness. Furthermore, 4 quadrants were arranged based on 1) the difficulty position of each element compared to the mean-score of difficulty and; 2) the usefulness position of each element compared to the mean-score of usefulness.Conclusion: The order of elements of e-learning at the Environmental Health School of Magetan based on priority were assignment, quiz and discussion forum as the first priority; feedback and survey as second priority; link to resources and book as third priority; and learning design, handout and chatting as the last priority.Keywords: health college, e-learning improvement, e-learning elements, prioritized elements